2012
DOI: 10.4028/www.scientific.net/amr.566.109
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Crack Propagation in PEEK Polymer Bearings under Water-Lubricated Conditions

Abstract: Radial ball bearings made of metal, ceramics and plastics are commonly used as important components in various types of industrial machinery. Due to the latest markets demands for elements capable of withstanding e.g. corrosive environment, metallic bearings are being gradually replaced by components produced from high performance engineering plastic polymers. In order to investigate the failure mechanism of polymer bearings and further improve their performance in practical applications in an underwater envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The test conditions of radial load and rotation speed were 90-360 N and 1200 rpm, respectively. They were the same as our previous works [9,14]. This is because the present tests were done in order to focus on the details of the fatigue fracture origin/propagation of the one-point RCF test.…”
Section: One-point Rolling Contact Fatigue Testmentioning
confidence: 99%
See 3 more Smart Citations
“…The test conditions of radial load and rotation speed were 90-360 N and 1200 rpm, respectively. They were the same as our previous works [9,14]. This is because the present tests were done in order to focus on the details of the fatigue fracture origin/propagation of the one-point RCF test.…”
Section: One-point Rolling Contact Fatigue Testmentioning
confidence: 99%
“…Dearn et al reported that the location of the maximum shear stress depended on the friction condition and was related with the fracture of PEEK polymer gears [8]. Flaking was related to the internal fatigue cracks which were caused by cyclic shear stress below the contact surface [9]. Koike et al stated that in the RCF of the PEEKalumina ball bearings with an artificial pit, the subsurface fatigue crack ocuured at 100-200 um depth from the contact surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the practical application research on PEEK's tribological fatigue fracture of the combination between PEEK plastic and ceramic part is only few studies [7][8][9]. In the previous study, we reported that the subsurface crack propagated along the PEEK shaft rolling direction in terms of fatigue failure mechanism when cyclic compressive stress was applied to the PEEK shaft [9].…”
Section: Introductionmentioning
confidence: 99%